Root caries in areas with and without fluoridated water at the Southeast region of São Paulo State, Brazil - Lilian Berta Rihs; Maria da Luz Rosário de Sousa; Ronaldo Seichi Wada (University of São Paulo, 2008)
This study aimed to investigate root caries prevalence in areas with and without water fluoridation at the Southeast region of São Paulo State, in the adult population, employees of public and private schools, and elderly population. Epidemiological surveys were conducted according to the World Health Organization guidelines (1997), including 1,475 dentate individuals aged 35 to 44 years and 65 to 74 years, living in cities representing the southeast of São Paulo State, with (n=872) or without (n=603) fluoridated water supply. Statistical analysis was performed by Mann-Whitney and Chi-square tests at a significance level of 5%. The prevalence of root caries was 15.6% for the 35-44-year-old age group and 31.8% for the 65-74-year-old age group . There were no statistically significant differences (p>0.05) in the occurrence of root caries according to water fluoridation, although individuals living at non-fluoridated areas presented higher percentage of missing teeth; also, there was higher mean number of intact roots at fluoridated areas (p<0.05). Most individuals with gingival recession, both adults and elderly, did not have root caries experience. In this study, root caries prevalence was lower in areas with fluoridated water. Due to the reduced prevalence of edentulism and increased number of people keeping their natural teeth for a longer period, a future increase in root caries is expected, highlighting the importance of studies related to water fluoridation and its relationship with the oral health of adults and elderly, especially referring to tooth root.